ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PENERAPAN ETIKA KEPERAWATAN DI RSUD ANUGERAH TOMOHON - Makausi, Estefina; Kalangi, Veronika; Rapar, Tesalonika (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Abstract –Introduction: Aspects of nursing ethics are important for a nurse when providing services to patients. Until now, there are still nurses who commit ethical violations, from falling patients, wrong injections, neglected patients, to late treatment. This is because nurses pay less attention to the ethical principles of nursing, which should be used as a guide in the implementation of nursing care. Purpose: The purpose of this research is to know the factors related to the application of nursing ethics in RSUD Anugerah Tomohon. Method: The research method used was cross-sectional; the sample in this study was 57 from a total population of 67 nurses. The sample was taken using stratified random sampling. This study used the Spearman’s rho test. Measuring tool in the form of a questionnaire.Results: According to the results of the study, there is no relationship between knowledge and the application of nursing ethics (0.650 > 0.05), there is a significant relationship between attitudes and the application of nursing ethics (0.004 < 0.05), and there is no relationship between tenure and the application of nursing ethics (0.499 > 0.05). Conclusion: In conclusion, there is no relationship between knowledge, tenure, and the application of nursing ethics; there is a significant relationship between attitudes and the application of nursing ethics in the RSUD Anugerah Tomohon